Posterior cruciate ligament injuries in the athlete: an anatomical, biomechanical and clinical review - Margheritini, F.; Rihn, J.; Musahl, V.; Mariani, P. P.; Harner C. (Sports Medicine, 2002)
Recently, the posterior cruciate ligament (PCL) has become an increasingly popular subject of orthopaedic research and debate. In the past several years, anatomic and biomechanical studies have provided invaluable information concerning the structure and function of the PCL. However, many aspects of PCL injury are still not fully understood. Diagnosis of the injury is often missed because of subtlety of symptoms and clinical findings, and current management strategies of PCL injury have experienced relatively poor clinical outcomes. Controversy exists concerning the most appropriate treatment, especially in cases of isolated PCL injury. The purpose of this review is to present a complete overview of the current knowledge regarding the basic science and clinical aspects of PCL injuries, with a specific focus on the athletic population.